The socio-economic impact of fungicide resistance in West Australia's Wheatbelt - Olita, Toto; Sung, Billy; Hooper, Bethany; Cao, Zhanglong; Lopez-Ruiz, Fran; Gibberd, Mark (Elsevier, 2023)
Farming is a risky business, demanding daily decisions on farm input expenditure and best practices while operating in an uncertain climate. One of these decisions regards agro-chemical inputs for disease control, a decision increasingly challenged by fungicide resistance for many pathogens of agricultural significance. To understand disease management decision-making and the importance of fungicide resistance, we surveyed 137 barley growers from West Australia's Wheatbelt. On average, this group spent AU$42/ha on fungicide application. Our survey found that growers were willing to invest an additional AU$18/ha to delay resistance of the pathogen to fungicides. Qualitative data show that barley growers perceive fungicide resistance as a growing issue in the region with a significant economic and emotional impact. Growers also expressed concern that fungicide resistance could become a long-term threat to the sustainability of their agribusiness. This study demonstrates that understanding growers' financial motivations and the economics of plant diseases is vital.